(untitled) (Physical Education, Health and Social Sciences, 2025)
Background: Optimal collaboration between pharmacists and other healthcare professionals such as physicians is integral in implementing pharmaceutical care. However, there are concerns regarding the role of pharmacists, especially among low- and middle-income countries. This study explored the perceptions, expectations, and experience of physicians working in various hospital settings of Punjab, Pakistan, about pharmacists and their roles. Methods: A self-administered questionnaire consisting of four sections was administered from April to July 2025. Descriptive and inferential statistics such as Kruskal- Wallis and Mann-Whitney tests were used for data analysis using SPSS. Results: Six hundred and seventy-eight physicians participated in this study with a response rate of 77.9%. Most of the physicians reported minimal to no interaction with pharmacists (n = 521, 76.8%). However, more than three-quarters of physicians (n = 660, 97.3%) accepted pharmacists as evidence-based sources of drug information. In addition, many physicians (n = 574, 84.7%) strongly agreed that pharmacists should attend patient care rounds to respond promptly to questions related to patient medication. A limited number of physicians (n = 124, 18.3%) assumed that pharmacists were advising their patients regarding the judicial use of their drugs. Median expectation and experience score had a significant association with age, experience, and education of physicians (P < 0.05). Conclusions: The perception of physicians was positive toward certain roles of pharmacists, coupled with high expectations. However, their experience was low, with most of the activities of pharmacists due to inadequate interprofessional coordination.